Dissociations Among Direct and Indirect Indicators of Adiposity in Young Wrestlers. Issue 2 (February 2015) - Cochrane, Kristen C.; Housh, Terry J.; Bergstrom, Haley C.; Jenkins, Nathaniel D.M.; Johnson, Glen O.; Housh, Dona J.; Traylor, Daniel A.; Lewis, Robert W.; Schmidt, Richard J.; Cramer, Joel T.
Abstract : Abstract: Cochrane, KC, Housh, TJ, Bergstrom, HC, Jenkins, NDM, Johnson, GO, Housh, DJ, Traylor, DA, Lewis, RW Jr, Schmidt, RJ, and Cramer, JT. Dissociations among direct and indirect indicators of adiposity in young wrestlers. J Strength Cond Res 29(2): 408–415, 2015—The purposes of this study were to: (a) examine the age-related patterns of differences in height (HT), body mass (BM), percent body fat (% fat), body mass index (BMI), and skinfolds (SF) in 11- to 18-year-old wrestlers; (b) determine the coherence of direct (% fat) and indirect (BMI and SFs) indicators of adiposity in the wrestlers; and (c) compare the age-related patterns and mean values for HT, BM, BMI, subscapular, and triceps SF for the wrestlers to those of national samples of boys from the National Health and Nutrition Examination Survey (NHANES) database. One hundred thirty wrestlers were divided into 8 independent yearly age groups (AG): AG11–AG18 years. Height, BM, BMI, subscapular SF, triceps SF, medial calf SF, thigh SF, sum of SFs, and % fat were assessed. There were no differences between the wrestlers and NHANES samples for age-related patterns of BMI (0.61 and 0.63 kg·m −2 ·y −1 ), subscapular SF (0.47 and 0.37 mm·y −1 ), or triceps SF (−0.31 and −0.39 mm·y −1 ). Furthermore, the wrestlers displayed no differences in % fat between age groups. The results indicated that: (a) dissociations existed between the direct and indirect indicators of adiposity; (b) the wrestlers were similar in height but had smaller upper-body SFs when compared with NHANES samples; and (c) participation in wrestling (1–8 years) had no adverse effects on the normal age-related growth patterns for HT, but favorable effects on measures of adiposity.